INOVAÇÃO TECNOLÓGICA APLICADA AOS MEIOS DE SOLUÇÃO DE CONFLITOS: SESSÕES DE MEDIAÇÃO POR VIDEOCONFERÊNCIA COMO FORMA DE DEMOCRATIZAÇÃO E EFETIVO ACESSO À JUSTIÇA NO PODER JUDICIÁRIO DE MATO GROSSO DO SUL ENTRE OS ANOS DE 2018 A JUNHO DE 2021. - GISELE GUTIERREZ DE OLIVEIRA ALBUQUERQUE (2022)
The objective is to analyze the effectiveness of Access to Justice and online Mediation by videoconference in the Court of Justice of Mato Grosso do Sul in the years 2018 to June 2021, using the theoretical framework of the Brazilian Consensual Microsystem and negotiation negotiation based on principles / integrative, in a transdisciplinary dialogue with legal pluralism and Warantian mediation. Research problem: to verify if the online mediation session by videoconference implemented by the Court of Justice of Mato Grosso do Sul and developed in the Judiciary Centers for Conflict Resolution and Citizenship is considered an adequate and sustainable means of effective access to justice in the South Judiciary. Mato Grosso do Sul. In conclusion, it appears that the Judiciary Branch of Mato Grosso do Sul contributes to the construction of a consensual culture with the implementation of a Dispute Treatment Policy committed to a more accessible and humane justice. Research with qualitative/quantitative dimensions and the deductiveinductive method are used.